Natural Becoming: From Bad Infinity Towards an Open Dialectic? Contemporary Issues Moving From Hegel’s Philosophy of Nature - Erle, Giorgio (ETHICS IN PROGRESS, 2024)
In Hegel’s Philosophy, natural time is the engine of bad infinity, presenting itself through disappearance. Nevertheless, as one proceeds towards the higher levels of the realm of exteriority, this force from abstract becomes increasingly real until it becomes part of vital processes in the organized subjectivity, such as that of the living organism that “knows” and uses this becoming as a force to its advantage, e.g., in the forms of metabolism. This effective meaning of natural becoming seems to us to have been particularly highlighted in the 20th–century in the “Philosophical Biology” of Hans Jonas, whereby even the elements of failure (e.g., in the animal’s procurement of food) are grasped as expressions of a distinctive trait of the subject, namely its capacity to bear the negative and with this to establish mediation. Even the mortal limit, which is what leads to the conclusion of the Naturphilosophie requiring the elevation to the Philosophy of Spirit in Hegel, according to Jonas, takes on, within the human awareness, a renewed ontological value that allows life to flourish again and with this makes human beings able to ask themselves what kind of world they want to hand over (also with environmental regard) to future generations. If this is the case, then a role for Naturphilosophie becomes highly topical about producing an “open dialectic” invoked many times in the philosophical paths of the 20th century.